Follicle-Stimulating Hormone Positively Associates with Metabolic Factors in Perimenopausal Women. (12th November 2020) - Zhang, Chen; Zhao, Meng; Li, Zhengyang; Song, Yongfeng
Abstract : Objective . Menopause is associated with the increased risk of metabolic syndrome (MetS) and cardiovascular (CV) disease. Most studies have focused the postmenopausal women and the relationships among estrogen, androgen, and Mets risk. The main aim of the study was to investigate the Mets risk in perimenopausal women and whether the variation of FSH is associated with metabolic factors. Methods . A single-center cross-sectional retrospective analysis including 154 premenopausal women and 124 perimenopausal women was performed. Results . The prevalence of Mets in the perimenopausal group was much higher than the premenopausal group (49.19% vs. 35.71%, p = 0.023 ). The prevalence of central obesity and NAFLD also increased in the perimenopausal group than in the premenopausal group. We grouped the population by FSH tertiles; compared with women in the lowest tertile, women in the highest tertile had higher age, WC, serum TC, LDL-C, AST, ALT, and creatine levels. The prevalence of hypertriglyceridemia, raised BP and Mets also increased in the highest tertile group. Further, we subdivided the perimenopausal women according to FSH tertiles. Compared with perimenopausal women in the lowest tertile, the prevalence of raised BP significantly increased in the highest tertile. Conclusions . The risk of Mets increased in perimenopausal females than in premenopausal women. And a higher FSH level was associated with higher WC, TG, BPs, and the risk of Mets in perimenopausal women. Elevated FSH level appears to be a risk factor of MetS biomarkers in perimenopausal women.